Hubungan Kemandirian Belajar dengan Motivasi Belajar Siswa Kelas Tinggi di Sekolah Dasar - satriani satriani; Adnan K Adnan K; Muh. Idris Jafar; asriadi asriadi (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This research is a descriptive quantitative research with correlational type which aims to determine whether there is a positive relationship between learning independence and student motivation at SDN 220 Cinnong, Sibulue District, Bone Regency. The population in this study were all students in grades IV, V and VI of SDN 220 Cinnong, Sibulue District, Bone Regency, which collected 41 students. The sampling technique in this study is non-probability sampling. Then based on the results of inferential statistical analysis obtained t count of 2.1404 and t table with a significance of 5%. of 1.684888 so that t count t table. It can be said that there is a positive relationship between learning independence and student motivation at SDN 220 Cinnong, Sibulue District, Bone Regency.